2013
DOI: 10.2139/ssrn.3039173
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Structural Change and Growth Relationship in India: State-Level Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…Cortuk and Singh (2015) undertake a similar analysis of the linkage between structural change and growth for the 16 states of India for the period 2000–2006. The authors found out that there is one-way positive impact from structural change to growth for the period 2000–2006.…”
Section: Review Of Literature On Structural Changes and Growthmentioning
confidence: 99%
“…Cortuk and Singh (2015) undertake a similar analysis of the linkage between structural change and growth for the 16 states of India for the period 2000–2006. The authors found out that there is one-way positive impact from structural change to growth for the period 2000–2006.…”
Section: Review Of Literature On Structural Changes and Growthmentioning
confidence: 99%
“…Using these “purer” measures of structural change, Cortuk and Singh (2011) conducted an empirical analysis for India that found causality from structural change to growth. Extending this approach to state-level growth performance, Cortuk and Singh (2015) found similar results with a panel regression analysis.…”
Section: Introduction [1]mentioning
confidence: 53%
“…As each change is counted twice, the scaling factor corrects for this and ensures that the measure lies between 0 and 1. In a departure from Cortuk and Singh (2011, 2015), in this paper, the index is calculated with respect to a fixed base year, so in the following empirical analysis, it is a cumulative measure rather than an annual change. This modification facilitates comparison with structural change calculations that are based on the McMillan–Rodrik approach, which are based on cumulative changes.…”
Section: Data Concepts and Stylized Factsmentioning
confidence: 99%
“…By using monthly data to study the relationship between industrial structure change and economic growth in Japan from 1978 to 2006, Nutahara [12] found that the long-term trend of industrial structure change has a significant correlation with economic growth and the emergence of new industries caused by new technologies in industrial structure change will generally lead to long-term economic growth. Cortuk and Singh [13] used panel data to study the relationship between industrial structure change and economic growth in India from 2000 to 2006, and found that the industrial structure change in this period had a positive impact on the economic growth rate.…”
Section: Related Literaturementioning
confidence: 99%